Comparación de extractos de propóleos ecuatorianos producidos por apis mellifera mediante cromatografía en capa delgada - Carrión Ríos, Brenda Isabel; Orellana Berrezueta, Victoria Noely (My University, 2024)
Propolis is a bee product composed of wax and vegetable exudates, mostly produced by bee species such as Apis Mellifera. According to the literature, it presents a remarkable chemical variability due to its botanical origin, which makes it a relevant subject of study. In Ecuador, this research is of special interest, since compounds have been identified in national propolis that are not found in those of other countries, due to the plant biodiversity of Ecuador. From a social and economic perspective, the need arose to implement accessible methods for the differentiation of propolis extracts, being thin layer chromatography (TLC) a viable alternative to more sophisticated but less accessible techniques. In this study, a TLC-based procedure was developed for the differentiation of Ecuadorian propolis extracts produced by Apis mellifera, applying different chromatographic conditions. The research followed a quasi-experimental and retrospective design, using representative samples of Ecuadorian propolis previously studied by high-performance liquid chromatography (HPLC), whose data complemented the analysis. Silica gel plates were used with fluorescent indicator (254 nm) on aluminum support and different developers such as: ultraviolet light (254 and 365 nm), sulfuric acid/vainillin/heat, ammonia, FeCl3, iodine and KMnO4 in basic medium. The analysis was complemented by comparison with 14 reference substances and confirmation of results by preparative TLC and HPLC-DAD. In addition, the antimicrobial activity of propolis extracts was evaluated by the Kirby-Bauer method. The results revealed that two mobile phases provided the best chromatographic separations. We were able to differentiate different propolis samples: sample P19 (Group I) showed matches with chrysin and CAPE in different physical and chemical revelations, which was confirmed by preparative TLC and HPLC-DAD. A similar procedure was performed on samples P20 (Group IV) and P5 (Group V), where the presence of sterbin and nemorosone, respectively, was demonstrated. In contrast, samples P6 (Group II) and P4 (Group III) showed similarities between them but could be differentiated taking into account the position of the most intense spots in the chromatograms. Sample P8, rich in triterpenes, could also be differentiated from the rest. As for the antimicrobial activity, the extracts did not show activity against S, aureus and E. Coli with the amounts evaluated. This study highlights the usefulness of TLC as an accessible technique for the differentiation of Ecuadorian propolis and opens the possibility of future research, such as the exploration with other reference substances that allow a more detailed characterization of the samples.
El propóleos es un producto apícola compuesto por cera y exudados vegetales mayormente, producido por especies de abejas como Apis mellifera. Según la literatura, presenta una notable variabilidad química debido a su origen botánico, lo que lo convierte en un tema relevante de estudio. En Ecuador, esta investigación cobra especial interés, ya que se han identificado compuestos en propóleos nacionales que no se encuentran en los de otros países, debido a la biodiversidad vegetal del Ecuador. Desde una perspectiva social y económica, surgió la necesidad de implementar métodos accesibles para la diferenciación de extractos de propóleos, siendo la cromatografía en capa delgada (CCD) una alternativa viable frente a técnicas más sofisticadas, pero menos accesibles. En este estudio, se desarrolló un procedimiento basado en CCD para la diferenciación de extractos de propóleos ecuatorianos producidos por Apis mellifera, aplicando diferentes condiciones cromatográficas. La investigación siguió un diseño cuasiexperimental y retrospectivo, utilizando muestras representativas de propóleos ecuatorianos previamente estudiadas mediante cromatografía líquida de alta eficiencia (CLAE), cuyos datos complementaron el análisis. Se emplearon placas de sílica gel con indicador fluorescente (254 nm) sobre soporte de aluminio y diferentes reveladores como: luz ultravioleta (254 y 365 nm), ácido sulfúrico/vainillina/calor, amoniaco, FeCl3, yodo y KMnO4 en medio básico. El análisis se complementa mediante la comparación con 14 sustancias de referencia y la confirmación de resultados mediante CCD preparativa y CLAE-DAD. Además, se evaluó la actividad antimicrobiana de los extractos de propóleos mediante el método de Kirby-Bauer. Los resultados revelaron que dos fases móviles proporcionaron las mejores separaciones cromatográficas. Se logró diferenciar distintas muestras de propóleos: la muestra P19 (Grupo I) mostró coincidencias con crisina y cafeato de fenetilo (CAPE) en diferentes revelados físicos y químicos, lo que se confirmó mediante CCD preparativa y CLAE-DAD. Un procedimiento similar se realizó en las muestras P20 (Grupo IV) y P5 (Grupo V), donde se demostró la presencia de sterbina y nemorosona, respectivamente. En contraste, las muestras P6 (Grupo II) y P4 (Grupo III) presentaron similitudes entre sí, pero pudieron ser diferenciadas teniendo en cuenta la posición de las manchas más intensas en los cromatogramas. La muestra P8, rica en triterpenos, también pudo ser diferenciada del resto. En cuanto a la actividad antimicrobiana, los extractos no mostraron actividad frente a S. aureus y E. Coli con las cantidades evaluadas. Este estudio destaca la utilidad de la CCD como una técnica accesible para la diferenciación de propóleos ecuatorianos y abre la posibilidad de futuras investigaciones, como la exploración con otras sustancias de referencia que permitan una caracterización más detallada de las muestras.
Keywords: PROPÓLEOS; CCD; CLAE; CROMATOGRAFÍA